(untitled) (Journal of Social Sciences Review, 2025)
The current study was designed to examine personality as a predictor of adjustment problems and decisional regret among doctors. It was proposed that personality traits would be associated with adjustment problems and decisional regret among doctors. Thus, a survey research design was utilized in this study. Purposive sampling was employed to select a sample of 200 private clinics and government clinics. Hospitals of Lahore and Gujrat districts of Punjab, Pakistan. The Big Five Inventory–2 Short Form (BFI-2-S) by John and Soto (2015), Scale of Adjustment for Adults by Naz, Bano, & Leghari (2018), and the Decision Regret Scale by Brehaut et al. (2003) were used for data collection. Correlation, regression, and neural network analyses were performed, using SPSS Version 27 for statistical analysis. The findings revealed that adjustment problems were significantly and negatively correlated with extraversion, agreeableness, conscientiousness, and openness-mindedness. Conversely, adjustment problems were positively correlated with negative emotionality. Decision regret, however, did not show any statistically significant correlation with adjustment problems or any of the Big Five personality traits. Regression analysis revealed that among the predictors, agreeableness and extraversion negatively predicted adjustment problems. Negative emotionality emerged as a significant positive predictor. Conscientiousness and open-mindedness to experience were not significant predictors of adjustment problems. The results of this study contribute to the comprehension of these phenomena among Pakistani doctors, underscoring Personality as the predictor of Adjustment Problems and Decisional Regret.